Land management semi-arid archipelago based on water carrying capacity: Studies on Labuan Bajo, East Nusa Tenggara - Farah Syuraih Muchtar; Hayati Sari Hasibuan; Philiphi de Rozari (Journal of Degraded and Mining Lands Management, 2023)
Archipelago areas have high marine tourism resource potential, so they are often exploited for tourism needs. The characteristics of the Labuan Bajo region in the form of islands with geomorphological conditions in the form of hills have the potential to reduce the carrying capacity of the environment. Regional development in Labuan Bajo, classified as a semi-arid area for tourism purposes, can potentially cause a clean water crisis. This study aimed to analyze the environmental carrying capacity related to water availability to support the development of the Labuan Bajo region to become a super-priority tourism destination. The research method used is quantitative in the form of spatial analysis, literature studies, and water-carrying capacity analysis based on the Decree of the Minister of Environment and Forestry No. 297 of 2019. The research data were obtained from field observations and government agencies. The results show that the carrying capacity of water in 56.87% of the area in West Manggarai Regency has a deficit status. Most areas experiencing a deficit are on the mainland of Flores Island, especially in the urban area of Labuan Bajo. This is due to low rainfall, low soil ability to absorb water, and high anthropogenic activity from both local residents and tourism activities. In addition, the content of salinity, detergent, and BOD (biological oxygen demand) in groundwater samples in the urban area of Labuan Bajo has exceeded the water quality standard threshold. The results of this study can be considered for policy directions related to land use for regional development in semi-arid island areas.